2022
DOI: 10.3390/ijms23042001
|View full text |Cite
|
Sign up to set email alerts
|

The Different Temozolomide Effects on Tumorigenesis Mechanisms of Pediatric Glioblastoma PBT24 and SF8628 Cell Tumor in CAM Model and on Cells In Vitro

Abstract: It is necessary to elucidate the individual effects of temozolomide (TMZ) on carcinogenesis and tumor resistance to chemotherapy mechanisms. The study aimed to investigate the TMZ 50 and 100 μM dose effect difference between PBT24 and SF8628 cell line high-grade pediatric glioblastoma (phGBM) xenografts in a chicken chorioallantoic membrane (CAM) model, on PCNA and EZH2 immunohistochemical expression in the tumor and on the expression of NKCC1, KCC2, E- and N-cadherin genes in TMZ-treated and control cell grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Recently the different temozolomide and valproic acid effects on tumorigenesis mechanisms have been reported, such as their effect on tumor growth, the histological expression of PCNA and EZH2 in tumor cells, Na-K-2Cl, K-Cl, and SLC5A8 co-transporter gene expression in pediatric glioblastoma PBT24 and SF8628 cell tumors on chick embryo chorioallantoic membranes (CAM) and on corresponding cells in vitro, highlighting the importance of studies on efficacy in the context of individualized anticancer therapy [ 37 , 38 ]. This study’s novelty lies in the differential effect of the active substance DCA‘s anions on PBT24 and SF8628 tumors on the CAM and the cells in vitro, comparing the differences in the impact of the studied NaDCA and MgDCA salts.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently the different temozolomide and valproic acid effects on tumorigenesis mechanisms have been reported, such as their effect on tumor growth, the histological expression of PCNA and EZH2 in tumor cells, Na-K-2Cl, K-Cl, and SLC5A8 co-transporter gene expression in pediatric glioblastoma PBT24 and SF8628 cell tumors on chick embryo chorioallantoic membranes (CAM) and on corresponding cells in vitro, highlighting the importance of studies on efficacy in the context of individualized anticancer therapy [ 37 , 38 ]. This study’s novelty lies in the differential effect of the active substance DCA‘s anions on PBT24 and SF8628 tumors on the CAM and the cells in vitro, comparing the differences in the impact of the studied NaDCA and MgDCA salts.…”
Section: Discussionmentioning
confidence: 99%
“…Such data suggest that EZH2 inhibitors in pediatric glioblastoma treatment should be investigated further [ 58 ]. We recently reported that TMZ did not alter EZH2 expression but significantly reduced PCNA expression in PBT24 and SF8628 tumors on CAM [ 37 ]. In the SF8628 control tumor, the correlation between EZH2 and p53 was solid and significant, while in the PBT24 control tumor, the correlation was weak and insignificant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations